A 3‐Fluoro‐4‐hexylthiophene‐Based Wide Bandgap Donor Polymer for 10.9% Efficiency Eco‐Friendly Nonfullerene Organic Solar Cells. Issue 9 (30th January 2019) - Yu, Jeong Eun; Jeon, Sung Jae; Choi, Jun Young; Han, Yong Woon; Ko, Eui Jin; Moon, Doo Kyung
Abstract: Nonfullerene organic solar cells (NFOSCs) are attracting increasing academic and industrial interest due to their potential uses for flexible and lightweight products using low‐cost roll‐to‐roll technology. In this work, two wide bandgap (WBG) polymers, namely P(fTh‐BDT)‐C6 and P(fTh‐2DBDT)‐C6, are designed and synthesized using benzodithiophene (BDT) derivatives. Good oxidation stability and high solubility are achieved by simultaneously introducing fluorine and alkyl chains to a single thiophene (Th) unit. Solid P(fTh‐2DBDT)‐C6 films present WBG optical absorption, suitable frontier orbital levels, and strong π–π stacking effects. In addition, P(fTh‐2DBDT)‐C6 exhibits good solubility in both halogenated and nonhalogenated solvents, suggesting its suitability as donor polymer for NFOSCs. The P(fTh‐2DBDT)‐C6:3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(5‐hexylthienyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene (ITIC‐Th) based device processed using chlorobenzene/1, 8‐diiodooctane (CB/DIO) exhibits a remarkably high power conversion efficiency (PCE) of 11.1%. Moreover, P(fTh‐2DBDT)‐C6:ITIC‐Th reaches a high PCE of 10.9% when processed using eco‐friendly solvents, such as o ‐xylene/diphenyl ether (DPE). The cell processed using CB/DIO maintains 100% efficiency after 1272 h, while that processed using o ‐xylene/DPE presents a 101% increase in efficiency after 768 h and excellent long‐term stability. The results of this study demonstrate that simultaneous fluorination and alkylation are effective methods for designing donor polymers appropriate for high‐performance NFOSCs. Abstract : Wide bandgap donor polymers employing a simultaneous fluorination and alkylation are demonstrated to be an effective technique to design the donor materials in application of polymer solar cells (PSCs). Specifically, P(fTh‐2DBDT)‐C6 shows a high efficiency and stability when introducing eco‐friendly solvent in nonfullerene PSCs.